Society and economy in ancient India : an epigraphic study of the Maitrakas (c. A.D. 475-775) - Verma, Nita. (New Delhi : Vikas Pub. House, 1992)
On the history of the Maitrakas of Valabhi, contemporaries of the later Gupta dynasty; study primarily based on the numerous inscriptions issued by the Maitrakas monarch.
Includes bibliographical references and index.
Keywords: Maitrakas -- History -- Sources; Inscriptions -- India; India -- History -- 324 B.C.-1000 A.D. -- Sources